Integration of mental health care in private not-for-profit health centres in Guinea, West Africa: a systemic entry point towards the delivery of more patient-centred care? - Abdoulaye Sow; Jeroen De Man; Myriam De Spiegelaere; Veerle Vanlerberghe; Bart Criel (BMC, 2020)
Abstract Background Patient-centred care is an essential component of quality of health care. We hypothesize that integration of a mental health care package into versatile first-line health care services can strengthen patient participation, an important dimension of patient-centred care. The objective of this study is to analyse whether consultations conducted by providers in facilities that integrated mental health care score higher in terms of patient participation. Methods This study was conducted in Guinea in 12 not-for-profit health centres, 4 of which had integrated a mental health care package (MH+) and 8 had not (MH-). The study involved 450 general curative consultations (175 in MH+ and 275 in MH- centres), conducted by 18 care providers (7 in MH+ and 11 in MH- centres). Patients were interviewed after the consultation on how they perceived their involvement in the consultation, using the Patient Participation Scale (PPS). The providers completed a self-administered questionnaire on their perception of patient's involvement in the consultation. We compared scores of the PPS between MH+ and MH- facilities and between patients and providers. Results The mean PPS score was 24.21 and 22.54 in MH+ and MH- health centres, respectively. Participation scores depended on both care providers and the health centres they work in. The patients consulting an MH+ centre were scoring higher on patient participation score than the ones of an MH- centre (adjusted odds ratio of 4.06 with a 95% CI of 1.17-14.10, p = 0.03). All care providers agreed they understood the patients' concerns, and patients shared this view. All patients agreed they wanted to be involved in the decision-making concerning their treatment; providers, however, were reluctant to do so. Conclusion Integrating a mental health care package into versatile first-line health services can promote more patient-centred care.